(untitled) (Palíndromo, 2022)
This visual essay presents a series of photos showing the process of taking off cement parts that cover a Sabiá nest found in a walk. The construction of this artwork is pervaded by my relationship with my mother, in a coexistence that evokes memories that turned into visual/textual production, in which I intend to blur limits between real and fictional. From internal conversations, in an intimate tone, this text addresses to a mother herself and to the nature where the memories accessed for this writing are set. With Jorge Luis Borges writings, I seek brief dialogues about time and memory, which, associated with Louise Bourgeois’s poetic, articulate fragmented writings about home. Gaston Bachelard brings theoretical contribution to think about home in this imaginary.